ANALISIS YURIDIS PERKAWINAN BAGI PASANGAN YANG SUDAH BERGANTI JENIS KELAMIN DI INDONESIA MENURUT UNDANG - UNDANG NO. 1 TAHUN 1974 TENTANG PERKAWINAN DAN HUKUM ISLAM - MOCHAMMAD FAUZI ALDY (PREMISE LAW JURNAL, 2017)
The research results show the Islamic Law views that transgender is illegitimate because it is contradictory to the Qoran Al Hujarat Verse 13, Buchari’s tradition relating to the sayings and deeds of The Prophet Muhammad and the ulemas’ view, especially, the legal decision of Indonesia Ulemas No. 03/UMNas-VII/MUI/2010. However, if the purpose is to repair the sex, it is legitimate/permitable. The legal consequence of transgender in Indonesia is based on Article 56, paragraph 1 of LawNo.1/2013 about the Amandement on Law No.23/2006 about the Population Administration is that those who transgender should apply for their new sex legitimacy to the Court and change their population data, especially, on the sex in the Demography and Civil Regestry Office by bringing along the legal decision. The Islamic Law views the marriage of those who perform sex reassignment surgery is illegitimate because in principlethey have married with the same sex. Keywords: Sex Reassignment, Marriage, Law No. 1/1974 and Islamic Laws